Experimental study on micro-crack initiation in photovoltaic polycrystalline silicon wafer. (1st March 2021) - Zhang, Yangbo; Liu, Qida; Hou, Junling; Ni, Yangdong; Yu, Yuanjie; Jaubert, Jean-Nicolas; Lajoie-Mazenc, Eric; Boyère, Emmanuel; Thomas, Metais; Zuo, Hong
Abstract: Brittle fracture of polycrystalline silicon wafer is critical to long-term reliability of electronic devices and solar cells for its wide use as components or substrates in semiconductor industry. In order to observe its initiation under loads, classical tensile test was modified by introducing the poly-methyl methacrylate (PMMA) layer to determine critical stress of the micro-crack initiation in the wafer. The method is verified by the finite element computation and then the fracture criterion of the maximum principal stress criterion for the wafer material is deduced from a series tests on the material strength. It was found that the existence of dislocations and impurities in the wafer significantly influence the threshold stress levels which is modeled by the Weibull distribution. Especially, micro-cracks are more likely to initiate in the dislocation position but not in the impurity position. The proposed method can be further extended for studying the tensile fracture and related issues on such brittle materials as ceramics, quartz, and ice.